Report of the 1973-73 Committee on Concepts and Standards- External Reporting. (The Accounting Review, 1974)
Abstract The article presents the text of the 1973 report of the American Accounting Association Committee on concepts and standards for external reporting. The treatment of uncertainty in accounting should perhaps be divided into two facets. First, there is the analytical process of observing certain selected characteristics of a factual situation for the purpose of assessing the degree of uncertainty which is inherent in the situation. Second, there is the process of designing financial reports so that the accountant's assessment of uncertainty is conveyed in the financial statements. The realization concept developed over the years as the means for dealing with uncertainty. In most instances, it was felt that recognition of profit or loss at the sales point was best since this often was the first point in the long chain of events where prediction of net cash flows was possible within accepted bounds. Exceptions to the sales point have been allowed, as previously indicated, but it should be noted that each of the realization points is an estimate and, as such, is subject to error.